Exploring ESG Disclosure: What? And Why? A Study of Leading European Public Hospitals - Wójtowicz, Katarzyna; Wójtowicz, Jan (Journal of Finance and Financial Law, 2024)
The purpose of the article. This article aims to examine the sustainability disclosure practices of public hospitals within the European Union. It aims to identify the scope and trends in environmental, social and governance (ESG) information reported by these hospitals on their official websites and analyze the influence of national frameworks on these practices. Methodology. The study employs a manual content analysis of the official websites of 50 public hospitals from EU Member States, selected from Newsweek’s The World’s Best Hospitals 2024 list. An ESG Disclosure Index (ESG DI) was developed to evaluate the extent of sustainability information disclosed. The index includes 36 items across various sustainability dimensions. Results of the research. The results show that the surveyed hospitals disclosed an average of 48% of the ESG metrics. Governance issues were disclosed the most (59%), followed by social (52%) and environmental (47%) dimensions. Scandinavian hospitals had a higher level of disclosure than their Southern European counterparts. The study highlights the fragmented nature of sustainability disclosure, which tends to report better performing indicators while selectively omitting others.